Comprehensive pharmacy review - Shargel, Leon, 1941- (Baltimore : Lippincott Williams & Wilkins, 2010)
Suitable for pharmacy students, from the first year of professional courses to preparation for the NAPLEX examination, this book may be used as a quick review or preview of essential topics by a diverse group of readers, including matriculation pharmacy students, instructors and preceptors, professional pharmacists, and foreign pharmacy graduates
Chapter 1 Drug Product Development in the Pharmaceutical Industry Chapter 2 Pharmaceutical Calculations and Statistics Chapter 3 Pharmaceutical Principles and Drug Dosage Forms Chapter 4 Biopharmaceutics and Drug Delivery Systems Chapter 5 Extemporaneous Prescription Compounding Chapter 6 Basic Pharmacokinetics Chapter 7 Bioavailability and Bioequivalence Chapter 8 Functional Group Chemistry and Biochemistry Chapter 9 Microbiology Chapter 10 Immunology Chapter 11 Biotechnology Drug Products Chapter 12 Principles of Pharmacodynamics and Medicinal Chemistry Chapter 13 Medicinal Chemistry and Pharmacology: Drugs Affecting the Nervous System Chapter 14 Autocoids and Their Antagonists, Nonnarcotic Analgesic--Antipyretics, and Nonsteroidal Anti-Inflammatory Drugs Chapter 15 Medicinal Chemistry and Pharmacology: Cardiovascular and Diuretic Drugs Chapter 16 Medicinal Chemistry and Pharmacology: Endocrinology and Related Drugs Chapter 17 Drug Metabolism, Prodrugs, and Pharmacogenetics Chapter 18 Drug-Drug and Drug-Nutrient Interactions Chapter 19 Nuclear Pharmacy Part II Chapter 20 Pharmaceutical Care and Disease State Management Chapter 21 Drug Information Resources Chapter 22 Adverse Drug Reaction Reporting Chapter 23 (new ch.) Medication Errors Chapter 24 Clinical Toxicology Chapter 25 Federal Pharmacy Law Chapter 26 Reviewing and Dispensing Prescriptions and Medication Orders Chapter 27 Sterile Products Chapter 28 Parapharmaceuticals, Home Diagnostics, and Medical Devices Chapter 29 OTC Otic, Dental, and Ophthalmic Agents (need to ask JC for (Figure 29.1: from Brunner & Suddarth's Textbook of Medical-Surgical Nursing - 10th edition (2004) Chart 58-10 Guidelines for Instilling Eye Medications) Chapter 30 OTC Dermatologic Agents Chapter 31 OTC Weight Control, Sleep Aids, and Smoking Cessation Chapter 32 OTC Agents for Fever, Pain, Cough, Cold, and Allergic Rhinitis Chapter 33 OTC Agents for Constipation, Diarrhea, Hemorrhoids, and Heartburn Chapter 34 OTC Menstrual, Vaginal, and Contraceptive Agents Chapter 35 Herbal Medicines & Nutritional Supplements Chapter 36 Clinical Pharmacokinetics and Therapeutic Drug Monitoring Chapter 37 Drug Use in Special Patient Populations: Pediatric, Pregnant, Geriatric Chapter 38 Common Clinical Laboratory Tests Chapter 39 Coronary Artery Disease Chapter 40 Cardiac Arrhythmias Chapter 41 Hypertension Chapter 42 Heart Failure Chapter 43 Thromboembolic Disease Chapter 44 Infectious Diseases Chapter 45 Seizure Disorders Chapter 46 Parkinson's Disease Chapter 47 Schizophrenia Chapter 48 Mood Disorders Chapter 49 Asthma and Chronic Obstructive Pulmonary Disease Chapter 50 Osteoarthritis and Rheumatoid Arthritis Chapter 51 Hyperuricemia and Gout Chapter 52 Peptic Ulcer Disease Chapter 53 (new ch.) Bowel Disorders Chapter 54 Diabetes Mellitus Chapter 55 Thyroid Disorders Chapter 56 Renal Failure Chapter 57 Cancer Chemotherapy Chapter 58 Pain Management Chapter 59 Nutrition and the Hospitalized Patient Chapter 60 Immunosuppressive Agents in Organ Transplantation Chapter 61 Outcomes Research and Pharmacoeconomics App. A App. B App. C App. D App. E
Includes index.
Keywords: Pharmacy -- Examinations, questions, etc; Pharmacy -- Examination Questions